Moving Toward Healthy Ageing: The Role of Physical Activity in Cognitive Function and Self-Esteem Among Older Adults in Türkiye - Okuyan, Canan Birimoglu; Kerkez, Müjde (UI Scholars Hub, 2025)
Background: This study aimed to evaluate the relationship between religious attitudes and breastfeeding attitudes and the effect of this relationship on breastfeeding practices. Methods: A cross-sectional study was conducted with 251 older adults. Data were collected using the International Physical Activity Questionnaire, the Standardized Mini-Mental State Examination, and the Rosenberg Self-Esteem Scale. Spearman’s correlation and chi-square tests were employed for statistical analysis. Results: Physical activity levels were positively correlated with both cognitive function (r = 0.546, p < 0.001) and self-esteem (r = 0.168, p < 0.05). No significant association was observed between cognitive function and self-esteem. Physical inactivity, cognitive decline, and low self-esteem were more prevalent among women, participants with lower educational attainment, those with chronic diseases, and individuals engaged in polypharmacy. Conclusions: The findings emphasize the importance of integrating physical activity promotion into national healthy ageing policies, particularly in Mediterranean contexts such as Türkiye. Implementing community-based exercise initiatives, strengthening primary care counseling, and developing culturally sensitive education programs can help reduce gender- and education-related disparities in physical activity participation.